2018
DOI: 10.1186/s13075-017-1503-x
|View full text |Cite
|
Sign up to set email alerts
|

BANK1 alters B cell responses and influences the interactions between B cells and induced T regulatory cells in mice with collagen-induced arthritis

Abstract: BackgroundFunctional variants of the B cell gene, B cell scaffold protein with ankyrin repeats 1 (BANK1) contribute to rheumatoid arthritis (RA) susceptibility, but their influences on B cell responses are unclear. Moreover, the function of induced T regulatory cells (iTregs) in the inflammatory milieu in a collagen-induced arthritis (CIA) model is unknown. This study was performed to investigate the roles of BANK1 in CIA and the interaction between B cells and iTregs.MethodsThe changes in BANK1 mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Utilizing classical markers B-lymphocyte antigen Cluster of Differentiation 19 (Cd19) and Ms4a1 [76,77], our analyses identified two clusters with B-lymphoid lineage identity (mNEC1 and mNEC6). They both showed the expression of immunoglobulin-like genes Immunoglobulin Kappa Constant (Igkc), Immunoglobulin Heavy Constant Mu (Ighm), Immunoglobulin Heavy Constant Delta (Ighd) and additional B-cell markers, such as Cd79a [78], Cluster of Differentiation 83 (Cd83) [79], B Cell Scaffold Protein with Ankyrin Repeats 1 (Bank1) [80], and Paired Box 5 (Pax5) [81] (Fig. 4C, and Supplementary Fig.…”
Section: Outlining the Diversity Of Non-epithelial Mammary Resident Cell Typesmentioning
confidence: 99%
“…Utilizing classical markers B-lymphocyte antigen Cluster of Differentiation 19 (Cd19) and Ms4a1 [76,77], our analyses identified two clusters with B-lymphoid lineage identity (mNEC1 and mNEC6). They both showed the expression of immunoglobulin-like genes Immunoglobulin Kappa Constant (Igkc), Immunoglobulin Heavy Constant Mu (Ighm), Immunoglobulin Heavy Constant Delta (Ighd) and additional B-cell markers, such as Cd79a [78], Cluster of Differentiation 83 (Cd83) [79], B Cell Scaffold Protein with Ankyrin Repeats 1 (Bank1) [80], and Paired Box 5 (Pax5) [81] (Fig. 4C, and Supplementary Fig.…”
Section: Outlining the Diversity Of Non-epithelial Mammary Resident Cell Typesmentioning
confidence: 99%
“…Verbal response test results were found to be high in cases with no expression level change between benign and non-BMS cases, and low levels of expression of BANK1 gene (11) which had an effect on B lymphocyte proliferation. The association of this factor with B cell functions is well known, but there are no studies showing its association with MS.…”
Section: Discussionmentioning
confidence: 91%
“…In this case, plasmablast and plasma cell production in lymphoid tissue is increased or memory cells in brain tissue start to produce pathogenic antibodies (6). Therefore, the most common B cell subtype found in MS plaques is a long-lasting plasma cell (11,15). The fact that monoclonal antibody-based treatment methods targeting B cells are effective in stopping the progression of the disease suggested that B cells also play a role in the development of disability (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sfrp4 , known to inhibit the Wnt pathway that controls cell proliferation, differentiation and migration, was downregulated following CIR 25 . The gene expression data do however also indicate that there is an ongoing injury ( Bank1, Il1a , and Pdgfra ) 1719 (Fig. 5), and all genes related to ECM were downregulated (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The thalamic astrocytes are presumably set to a healing state, with activated clearance mechanisms and lower levels of inflammation, as indicated by increased levels of Nov , Gpnmb, Ces2f and Ephx1 1316 . However, some genes ( Bank1, Il1a , and Pdgfra ) indicate that there is still an ongoing injury present as long as 4 months following CIR 1719 .…”
Section: Resultsmentioning
confidence: 99%